2018
DOI: 10.1016/j.stem.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Radial Glial Fibers Promote Neuronal Migration and Functional Recovery after Neonatal Brain Injury

Abstract: Radial glia (RG) are embryonic neural stem cells (NSCs) that produce neuroblasts and provide fibers that act as a scaffold for neuroblast migration during embryonic development. Although they normally disappear soon after birth, here we found that RG fibers can persist in injured neonatal mouse brains and act as a scaffold for postnatal ventricular-subventricular zone (V-SVZ)-derived neuroblasts that migrate to the lesion site. This injury-induced maintenance of RG fibers has a limited time window during post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 43 publications
2
94
0
Order By: Relevance
“…Our study showed that radial glial fibers are transiently maintained after neonatal brain injury, but not after adult brain injury (Jinnou et al . ). Although the mechanisms of radial glial maintenance are unknown, fibroblast growth factor signaling might be involved in maintaining radial glial fibers after chronic neonatal hypoxia (Ganat et al .…”
Section: Neuronal Migration After Neonatal Brain Injurymentioning
confidence: 97%
See 4 more Smart Citations
“…Our study showed that radial glial fibers are transiently maintained after neonatal brain injury, but not after adult brain injury (Jinnou et al . ). Although the mechanisms of radial glial maintenance are unknown, fibroblast growth factor signaling might be involved in maintaining radial glial fibers after chronic neonatal hypoxia (Ganat et al .…”
Section: Neuronal Migration After Neonatal Brain Injurymentioning
confidence: 97%
“…This N‐cadherin‐containing scaffold promoted SEZ‐derived neuroblast migration in the injured brain (Jinnou et al . ). Moreover, the transplanted N‐cadherin‐containing scaffold within the lesion promoted SEZ‐derived neuronal maturation and successfully improved gait disturbance in neonatal mice, but not in adult mice.…”
Section: Enhancement Of Neuronal Migration and Perspectivesmentioning
confidence: 97%
See 3 more Smart Citations